PENERAPAN PEMBELAJARAN FISIKA BERBASIS LINGKUNGAN DENGAN MODEL DISCOVERY LEARNING PADA MATERI FLUIDA STATIS - Tuuk, Savira Octavia; Marianus; Rende, Jeane Cornelda (Charm Sains: Jurnal Pendidikan Fisika, 2025)
The purpose of this study is to determine the improvement in learning outcomes of the application of environmental physics learning with the discovery learning model on static fluid material. The research method used is pre-experimental research with a one group pre-test post-test design. This research was carried out in three stages. The first stage is by giving a pre-test to measure the initial ability of students, the second stage is giving treatment by using an environment based physics learning strategy with discovery learning model. The third stage is giving a post-test to measure the learning outcomes of the students as well as an evaluation of the learning done. The subjects of this study were students of Class XI F1 at SMA Negeri 1 Remboken. Based on the data analysis conducted using paired samples T-test obtained sig value. (2-tailed) 0.000 <0.05 so H0 is rejected and H1 is accepted. Based on the results of the study, it can be concluded that environment-based physics learning with the Discovery Learning model on static fluid material can improve the learning outcomes of students in Grade XI at SMA Negeri 1 Remboken.